2019
DOI: 10.1038/s41598-019-50434-3
|View full text |Cite
|
Sign up to set email alerts
|

Realization of broadband negative refraction in visible range using vertically stacked hyperbolic metamaterials

Abstract: Negative refraction has generated much interest recently with its unprecedented optical phenomenon. However, a broadband negative refraction has been challenging because they mainly involve optical resonances. This paper reports the realization of broadband negative refraction in the visible spectrum by using vertically-stacked metal-dielectric multilayer structures. Such structure exploits the characteristics of the constituent metal and dielectric materials, and does not require resonance to achieve negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…Previous works have discussed the dependence of the effective properties on the metamaterial thickness, this is, on the number of MIM cavities composing the structure. [ 29,32–34 ] It has been shown that by reaching a minimum number of stacked layers, the multilayered fishnet metamaterials converge to the so‐known bulk metamaterial regime. [ 28,35 ] At this limit, metamaterials present unambiguous effective properties independently of the number of unit cells or the angle of incidence, exhibiting weak angular dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have discussed the dependence of the effective properties on the metamaterial thickness, this is, on the number of MIM cavities composing the structure. [ 29,32–34 ] It has been shown that by reaching a minimum number of stacked layers, the multilayered fishnet metamaterials converge to the so‐known bulk metamaterial regime. [ 28,35 ] At this limit, metamaterials present unambiguous effective properties independently of the number of unit cells or the angle of incidence, exhibiting weak angular dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…BPPs with large wave vectors propagate into pre-designed bulk hyperbolic metamaterials (HMMs) [ 111 ]. HMMs composed of alternatively deposited metal/dielectric multilayers exhibit a hyperbolic dispersion instead of elliptical dispersion, allowing for a larger-area and uniform deep subwavelength pattern to be generated inside a photoresist [ 34 , 112 ]. So far, 45 nm and 25 nm resolutions of half-pitch ( and ) have been fabricated and simulated with different interference patterns, respectively [ 113 ].…”
Section: Optical Methodsmentioning
confidence: 99%
“…If each layer is sufficiently small compared to the working wavelength, a vertical HMM can be considered an anisotropic homogenous medium. The permittivities can be calculated using EMT expressed as [ 36,38,39 ] εfalse∥=fεnormald+false(1ffalse)εnormalm ε=εnormaldεnormalmfεnormalm+false(1ffalse)εnormaldwhere ɛ ∥ is the effective permittivity along the parallel direction of the layer, ɛ ⊥ is the effective permittivity along the perpendicular direction of the layer, ɛ d is the permittivity of the dielectric material, ɛ m is the permittivity of the metallic material, and f is the filling ratio of the dielectric to metal. However, if each layer is not sufficiently thin, complex optical phenomena appear at the interfaces such as reflection and diffraction.…”
Section: Numerical Analysismentioning
confidence: 99%
“…The dispersion relation of the vertical HMM for transverse‐magnetic (TM)‐polarized light is described as [ 36 ] kx2+ky2ε+kz2ε=k02=()ωc2where k x , k y , k z are directional wave vectors in the HMM, k 0 is a wave vector in vacuum, ω is an angular frequency, and c is the speed of light in vacuum. The direction of ɛ ⊥ is parallel to the z ‐direction.…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation